2020
DOI: 10.2196/15994
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Decision Aid (myAID) to Enhance Quality of Life, Empowerment, Decision Making, and Disease Control for Patients With Ulcerative Colitis: Protocol for a Cluster Randomized Controlled Trial

Abstract: Background Patients with ulcerative colitis (UC) often face complex treatment decisions. Although shared decision making (SDM) is considered important, tools to facilitate this are currently lacking for UC. A recent pilot study of a novel Web-based decision aid (DA), my Actively Informed Decision (myAID), has suggested its acceptability and feasibility for informing treatment decisions and facilitating SDM in clinical practice. Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…3 Siegel and colleagues have led in this field through their development and validation of electronic decision aids for both ulcerative colitis and Crohn's disease. 1,4 Our multi-national research team has identified a role for a decision aid to guide patients with IBD to navigate decisions in the context of reproduction. This is on the background of a higher rate of voluntary childlessness amongst women with IBD, with contributors of poor knowledge as well as fears surrounding fertility, medications, inheritance, and delivery.…”
Section: E T T E R T O T H E E D I T O R Letter: Expanding the Role F...mentioning
confidence: 99%
“…3 Siegel and colleagues have led in this field through their development and validation of electronic decision aids for both ulcerative colitis and Crohn's disease. 1,4 Our multi-national research team has identified a role for a decision aid to guide patients with IBD to navigate decisions in the context of reproduction. This is on the background of a higher rate of voluntary childlessness amongst women with IBD, with contributors of poor knowledge as well as fears surrounding fertility, medications, inheritance, and delivery.…”
Section: E T T E R T O T H E E D I T O R Letter: Expanding the Role F...mentioning
confidence: 99%
“…Visual decision aids were considered to be important decision-making facilitators by the DECIDE patient stakeholders and the independent decision-making expert in view of the potentially overwhelming amount of technical details about the management options and the risk information that needs to be conveyed. Paper and web-based visual aids have been shown to facilitate confident decision-making in IBD patients choosing between surgical and/or medical options for symptomatic IBD [174][175][176] . None are specifically relevant for dysplasia with asymptomatic colitis and so we have developed a new patient-facing decision aid to help support decision-making, including signposting to patient support groups or charities (Supplementary Appendices 5).…”
Section: Supporting Decision-making Post-consultationmentioning
confidence: 99%
“…The work builds on our previous findings that: People on specialist outpatient waitlists actively engage in screening and hospital directed self-management (IBS) ( 11 ) Consumers and their regular doctors already use decision support tools ( 11 , 12 ) Digital technology is a feasible, acceptable and effective mode of facilitating the above ( 13 ). We describe here the codesign and initial user testing of the My PreHab Program , and assess its feasibility, acceptability, and appropriateness for consumers referred for orthopaedic assessment for total hip or knee replacement surgery.…”
Section: Introductionmentioning
confidence: 96%